(untitled) (The Harvest, 2022)
Workers’ participation in the management of jute industry of Nepal, an intensive scientific inquiry, was started by the researchers long years back to explore status and position of workers’ involvement in decision making. The major objectives of the study were; i. to assess the existing and desired degree and level of workers’ participation in different selected areas of decisions (i.e. economic , personnel and social decisions) in the units of the study (Biratnagar Jute Mills and Raghupati Jute Mills, each from private and public sector) at various levels as perceived by workers and management personnel, ii. to identify the degree and extent of involvement/ participation of workers in selected decision areas iii. to ascertain the management level of acceptance for workers’ participation, and iv. to assess and evaluate the effective performance of work committees as to overcome the barriers of participation. The study showed a poor level of workers’ participation in areas of personnel and economic decisions. However, their participatory desired level on this issue was quite high. A greater discrepancy between workers desired level of participation and management acceptance for participation indicated lack of mutual understanding among them. Similarly, works communities in both mills were not contributing at satisfactory level to both the parties as an effective mechanism of participation.